Late Paleocene pipe swarm in the Great South – Canterbury Basin (New Zealand) - Bertoni, C; Gan, Y; Paganoni, M; Mayer, J; Cartwright, J; Martin, J; Van Rensbergen, P; Wunderlich, A; Clare, A (Elsevier, 2019)
We have identified a deeply buried fluid escape pipe province in Cretaceous - late Paleocene sediments of the Great South–Canterbury Basin (NZ). The seismic observations and interpretations point to an unusually vast fossil system of pipes. These features are exceptional in number (>2000 edifices) and appear to have formed from a common root zone. The areal extent of the analysed pipe system (2500 km2) is among the largest systems of fluid expulsion features ever observed in three-dimensional seismic data.